Harlan County war - Parks, Van Dyke 1943- (Metrodome Distribution, 2007)
Dramatization of one family's struggle during the 1973 coal miner's strike in Harlan County, Kentucky
Original: USA, 2000
Sprache: englisch
Keywords: Coal Miners' Strike (Harlan County, Kentucky : 1973); Coal Miners' Strike, Harlan County, Ky., 1973 / Drama; Strikes and lockouts / Kentucky / Drama; Film adaptations; Television adaptations; Films for the hearing impaired; Feature films; Strikes and lockouts; Kentucky; Kentucky / Harlan County; Film; DVD-Video